Social housing and the principles of healthy city - Sperandio, Ana Maria Girotti; Rodrigues, Ana Carolina; Vitarelli, Lara Vilela (National Journal of City Management, 2025)
Objective – To assess how the Nelson Mandela Social Housing scheme (Campinas, Brazil)—composed of 15 m² “embryo” dwellings—aligns with healthy city principles and urban health promotion agendas. Methodology – Documentary and literature review combined with a field-based experience report. The “Mandala Conceitual Sperandio” was applied as the analytic framework to appraise dwelling design and immediate surroundings through the intangible elements of a healthy city. Originality/Relevance – The study advances debates on Brazilian social housing by operationalising a holistic, health-centred framework in a real-world case marked by micro-dwelling typologies and post-eviction resettlement, foregrounding intersectoral governance and social participation gaps. Results – While the scheme regularised tenure and provided basic networks, the typology neglects key health determinants: limited privacy, inadequate cross-ventilation, and ceiling heights that hinder safe expansion. The promised technical assistance for enlargement was not delivered, prompting precarious self-construction. Urban context weaknesses include sparse tree cover and limited connectivity, despite some public transport and social facilities nearby. Overall, the 15 m² units fall short of minimum habitability for diverse, often large, households, reinforcing urban inequalities rather than advancing health promotion. Theoretical/Methodological Contributions – Demonstrates the utility of the “Mandala Conceitual Sperandio” for integrating urban planning and health promotion, linking local housing assessment to WHO/PAHO/UN-Habitat guidance in a transferable evaluative approach. Social and Environmental Contributions – Points to the need for integrated housing policies that couple environmental comfort (airflow, daylight, thermal performance) with infrastructure provision, community participation and intersectoral governance, to safeguard wellbeing and equity in social housing delivery.